Safety and efficacy of Biacton® (Lactobacillus farciminis CNCM I‐3740) as a feed additive for weaned piglets. (8th May 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Biacton ® when used as a feed additive for weaned piglets. Biacton ® is a preparation of viable cells of Lactobacillus farciminis CNCM I‐3740 intended to be incorporated into feed for weaned piglets at a minimum recommended application level of 1 × 10 9 CFU/kg complete feed. L. farciminis is a species considered by EFSA to be suitable for the Qualified Presumption of Safety (QPS) approach to safety assessment which requires the identity of the strain to be conclusively established and evidence that it does not show acquired resistance to antibiotics of human and veterinary importance. The strain was found to meet the criteria for the QPS approach to safety assessment and since concerns are not expected from other components of the additive, the additive is presumed safe for all target species, consumers and the environment. Biacton ® is not irritant to skin, eyes or to the respiratory tract, but should be considered a prespiratory sensitiser. In the absence of data, no conclusions could be drawn on the potential skin sensitisation potential of the additive. No conclusion can be drawn on the efficacy of Biacton ® for weaned piglets based on the data available.